Coronary revascularization in Kawasaki´´ s disease - Cabrera Cerna, Carolina Del Rocío (2020)
Kawasaki´s disease (KD) has surpassed rheumatic fever in many countries as the first cause of acquired heart disease in pediatric age, being the coronary aneurism its worst complication. We present a case of successful revascularization in a 5-year-old patient, with three-vessel coronary disease secondary to KD, who underwent a coronary bypass with anastomosis from the left internal mammary artery to the anterior descending artery, the right mammary artery to the marginal obtuse artery and the radial artery to the posterior descending artery. Close follow-up and choosing the right time to undergo surgery will prevent adverse events like permanent disability of the patient, ventricular dysfunction, arrhythmias, global infarction and sudden death.